Effectiveness of Land and Building Tax Management in Oeteta Village, Sulamu District, Kupang District - TAFAE, Desy Lorenci; ROZARI, Petrus de; LINO, Maria M. (Journal of Governance, Taxation and Auditing, 2024)
This research aims to determine the effectiveness of Land and building tax management in Oeteta Village, Sulamu District, Kupang Regency. To discuss the results of this research, Terry (2006:342) used management functions, namely planning, organizing, implementing and controlling, then explained using Jogiyanto's (2017) system theory, namely input, process and performance results. The research method uses a qualitative description approach, combining data collection techniques, namely observation, interviews and literature study. Data analysis is inductive/qualitative, with an interactive model created by Miles, Huberman, and Sugiyono (2012: 246). The results of the research emphasize the meaning of generalization, which shows that (1) Input through cooperation and coordination between BAPENDA, the Sulamu Regency government and Oeteta Village, provision of counter facilities at the Village Office and human resources by determining tax collectors from the District and 3 RT people in Oeteta village. (2) the process of organizing and mobilizing is in the payment and collection of taxes, where fraud, irregularities and violations occur regarding the use of tax money by PBB collectors for personal needs. (3) output: There is no strict supervision by BAPENDA of billing officers, and there needs to be reporting from Oeteta Village and Sulamu District to BAPENDA Kupang Regency so that they can be accounted for. Based on the description above, BAPENDA's supervision can be further improved. The attitude of PBB collection officers and the absence of strict tax sanctions result in the misuse of tax money, so the public/taxpayers do not want to pay PBB.